Maggie and the unicorn - Baker, E. D. (London : Bloomsbury, 2017)
When Maggie and her friend, Bob, learn of an injured unicorn in the forest, they set off to rescue him but Maggie's stepbrother, Peter, plans to stop them.
Primary
Fiction
Keywords: Magic -- Fiction; Animals, mythical -- Fiction; Stables -- Fiction; Stepbrothers -- Fiction; Unicorns -- Fiction